2003
DOI: 10.1023/a:1022916310694
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumor, Lung and Kidney Retention and Antimetastasis Effect of NAMI-A Following Different Routes of Administration

Abstract: Imidazolium-trans-dimethylsulfoxideimidazoletetrachlororuthenate (NAMI-A) is a ruthenium compound effective on solid tumor metastases. In this study, we evaluated the effects of different routes of administration of NAMI-A on the distribution to primary tumor, lungs and kidneys in BD2F1 hybrids with Lewis lung carcinoma or in CBA inbred mice with MCa mammary carcinoma. NAMI-A concentration and the percentage of cumulative dose (%Dtot) retained in these tissues is independent of the animal strain and of the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…[18] Imidazolium trans-[tetrachloro (DMSO)(imidazole)ruthenate(III)], NAMI-A, binds within minutes to plasma proteins, [19] inhibits lung metastases formation and reduces metastases weight without affecting the primary tumour. [20] Indeed, both in vitro and in vivo data appear to exclude DNA as the primary target, in line with the observation that the binding of NAMI-A to DNA is much weaker than platinum complexes. [21] KP1019 and NAMI-A are both progressing through clinical trials.…”
Section: Introductionmentioning
confidence: 61%
“…[18] Imidazolium trans-[tetrachloro (DMSO)(imidazole)ruthenate(III)], NAMI-A, binds within minutes to plasma proteins, [19] inhibits lung metastases formation and reduces metastases weight without affecting the primary tumour. [20] Indeed, both in vitro and in vivo data appear to exclude DNA as the primary target, in line with the observation that the binding of NAMI-A to DNA is much weaker than platinum complexes. [21] KP1019 and NAMI-A are both progressing through clinical trials.…”
Section: Introductionmentioning
confidence: 61%
“…The cellular effects of NAMI‐A that typically correlate with the in vivo antimetastatic activity were detected at doses 100 to 1000 times below those inducing cytotoxicity , , . Preclinical studies demonstrated that the effect of NAMI‐A in metastasis inhibition was independent of the administered dose, both in terms of frequency and in terms of route of administration . Finally, in the clinical studies the cases of stable disease (phase I) and partial response (phase I/II) were all found at the lowest doses of NAMI‐A.…”
Section: Results Of Clinical Investigationsmentioning
confidence: 97%
“…1). Both compounds behave quite differently to cisplatin; NAMI-A inhibits growth of metastatic tumours [8], while KP1019 is active in colorectal tumours where cisplatin exhibits limited activity [9]. Protein binding, especially to transport proteins, appears to be essential for the modes of action of certain ruthenium anticancer agents [10].…”
Section: Introductionmentioning
confidence: 99%